The Influence of Work-Life Balance, Employee Engagement, and Job Satisfaction on Improving Job Performance of Manufacturing Company Employees - Dheni Hermaen; Arsadi; Subandriyo; Faye Maya Dewi; Lod Sulivyo (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To determine the influence and relationship that will improve job performance through the role of work-life balance, employee engagement and job satisfaction. Background Problem: In managing human resources in the industry, how can workers improve their performance by deepening the importance of employee performance in improving the company's work results. Novelty: Conducting tests in the manufacturing industry sector with analysis tools using smartPLS. Research Method: Using quantitative methods with the SEM (Structural Equation Model) method, conducting discriminant validity analysis, Squareroot of Average Variance Extracted (AVE), conducting Variance Inflating Factor (VIF) analysis, composite reliability (CR), then conducting R square and T-statistic analysis. Findings/Results: That there is a significant influence that can improve the company's work performance including life balance, employee engagement and job satisfaction. Conclusion: Companies need to improve employee work performance by paying attention to employee life balance very well and wisely.